INVENTARISASI DAN PEMETAAN POHON ULIN (Eusideroxylon zwageri Teijsm. & Binn.) DI KEBUN RAYA UNMUL SAMARINDA (KRUS) PROVINSI KALIMANTAN TIMUR - Yena Qodaryana dan Heni Emawati (Universitas 17 Agustus 1945 Samarinda, 2015)
Inventory and Ulin (Eusideroxylon zwageri Teijsm. Et Binn.) Mapping at Botanic Gardens of Unmul Samarinda (KRUS) East Kalimantan Province.The purpose of this study was to determined the diversity of flora especially Ulin trees species (E. zwageri), knowing the potential of Ulin trees species in the plots study and mapping the distribution of the presence of Ulin trees species so that can be basic for KRUS managers to implementing the policy.The object of research in the plots study in KRUS with transects method. Transects were made along each ± 1.000 m, width 20 m, which begins by taking the initial point. The data collected were of primary data at the level inventory of Ulin poles and tree trunks that were ≥ 10 cm in diameter. The data includes the number of individuals captured, the diameter of the tree trunk, bole height and total tree height, while secondary data was obtained directly from the results of previous studies, literature, and writing reports from the relevant agencies that include the location of the area, soil conditions, geogarafi conditions, climate, rainfall and vegetation. As well as interview methods used to obtain the data and information from officers in the field, officials concerned agencies and local residents that has to do with the activities of research and literature support.The results of the research are 1) The diameter of the largest Ulin was 86.1 cm with a total volume of 8.31 m³ found on transect A, while the smallest diameter was 11.3 cm with a total volume of 0.04 m³ which found on transect C. The potential of Ulin can be seen from the number of bole height that found in the observation area in 6 ha were 27.65 m³, while the total volume amounted to 55.86 m³; 2) Distribution of Ulin at KRUS most common in conservation zone covering an area of 3.48 hectares with 11 trees, at collection zone enrichment covering an area 2.24 ha with 10 trees and at recreation zone covering an area 0.28 ha with 8 trees.